Relaxations in relation to Liquid Crystalline Formation and Glass Transition for Comb-like Polymer: Structural Relaxation as expressed by Entropy Model and Activation Energy Spectrum - Tanaka, Yutaka (Journal of Nepal Chemical Society, 2013)
This study demonstrates that the modelling approach for the kinetic phenomenon of glass transition is effective to examine the relaxation. In the enthalpy relaxation of poly(cyanobiphenyl-yloxy) alkyl acrylate, the decrease in enthalpy was measured as a function of ageing time and ageing temperature. Obtained data was analysed at first with the activation energy spectrum (AES) model, and next, with the framework of the entropy model which follows the evolution of the configurational entropy of the sample during the whole thermal history in the experiment. The prediction of DSC curve based on the result of analysis for the glass transition will be presented. AES model gives information about thermally activated processes which are available to contribute to observed enthalpy changes against the thermal history. The activated processes are relevant to the rearrangement of molecules. The rearrangement corresponds to the structural changes of polymer chain which can be observed in our study as the change in optical texture, known as the coarsening dynamics of nematic domain for the liquid crystalline materials. The analysis for the coarsening is also shown to elucidate the specific feature of physical parameter.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9377Journal of Nepal Chemical Society Vol. 30, 2012 Page:  107-110 Uploaded date: 12/19/2013